THE EFFECTIVENESS OF THE 3R (REDUCE, REUSE, AND RECYCLE) PROGRAM IMPLEMENTED THROUGH WASTE BANKS IN EMPOWERING THE COMMUNITY ECONOMY IN GORONTALO (A Case Study of Parent Waste Bank in Wongkaditi Timur Kota Utara Gorontalo) - Sabihi, Syaiful B.; Husain, Walidun; Wantu, Sastro Mustapa (Public Policy Journal, 2020)
This research aims to analyze and describe (1) the effectiveness of the 3R program implemented through waste banks in empowering the community economy in Gorontalo and (2) the supporting and inhibiting factors of the 3R program implemented through waste banks in empowering the community economy in Gorontalo. The research method used is qualitative. The research data source is primary data collected using interviews. The data analysis technique used refers to Miles and Huberman’s. The research findings are that (1) the 3R (reduce, reuse, and recycle) program implemented through waste banks has effectively empowered the community economy in Gorontalo. The program is progressively developed, indicated by the fact that waste in Gorontalo has been reduced to the target determined. Contrastively, the city management system comprising selecting, transporting, and processing is still poor. In terms of the economic use, the system does not give significant contributions to the economic improvement of the surrounding community that becomes the customer of waste banks and (2) the crucial internal factors of the 3R program the waste bank owner’s commitment to introducing the program and the employees’ commitment to earning the incentive. Meanwhile, the inhibiting factors are the narrow waste banks and insufficient tools and facilities that support the 3R (reduce, reuse, and recycle) program. Furthermore, the external factors are the government, the cooperation with the waste bank owners in Gorontalo, and a fixed market share where the waste can be sold. Moreover, the inhibiting factors are the community’s perception of waste banks. They perceive small uses of the waste banks and they reluctantly spare time to sell waste in waste banks.